2010
DOI: 10.1161/atvbaha.110.206011
|View full text |Cite
|
Sign up to set email alerts
|

Single Administration of the CXC Chemokine-Binding Protein Evasin-3 During Ischemia Prevents Myocardial Reperfusion Injury in Mice

Abstract: Objective-Evasins (chemokine-binding proteins) have been shown to selectively neutralize chemokine bioactivity. We investigated the potential benefits of Evasin-3 on mouse myocardial ischemia/reperfusion injury. Methods and Results-In vivo and ex vivo (Langendorff model) left coronary artery ligature was performed in C57Bl/6 mice. Coronary occlusion was maintained for 30 minutes, followed by different times (up to 24 hours) of reperfusion. Five minutes after coronary occlusion, mice received 1 intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 37 publications
6
76
1
Order By: Relevance
“…The dose of Evasin-3 administered was based on previous studies, showing marked efficacy to reduce in vivo neutrophil infiltration within inflamed tissues. 8,9 After 45 minutes of transient middle cerebral artery occlusion, blood flow was restored by the withdrawal of the nylon suture ( Figure 1B). A return to 450% of baseline regional cerebral blood flow within 5 minutes of suture withdrawal confirmed a reperfusion of the middle cerebral artery territory.…”
Section: Materials and Methods Prevention Strategy: Treatment With Evmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of Evasin-3 administered was based on previous studies, showing marked efficacy to reduce in vivo neutrophil infiltration within inflamed tissues. 8,9 After 45 minutes of transient middle cerebral artery occlusion, blood flow was restored by the withdrawal of the nylon suture ( Figure 1B). A return to 450% of baseline regional cerebral blood flow within 5 minutes of suture withdrawal confirmed a reperfusion of the middle cerebral artery territory.…”
Section: Materials and Methods Prevention Strategy: Treatment With Evmentioning
confidence: 99%
“…Since common inflammatory pathways have been recently indicated as promising pathophysiological targets for both prevention and treatment in ischemic stroke, 7 we focused on the pharmacological inhibition of CXC chemokines (mainly CXCL1 and CXCL2, which have been shown as the major leukocyte chemoattractants and activators). 8 In particular, we used the selective CXC chemokinebinding protein Evasin-3 (which has been recently shown to potently inhibit neutrophil-mediated cardiac injury after an acute myocardial infarction) 9 to abrogate CXC chemokine bioactivity in both prevention and treatment of ischemic stroke. Two validated mouse models (shear stress-induced carotid atherogenesis developing both vulnerable and stable plaques and transient focal cerebral ischemia) 10,11 were used to assess the potential benefits of Evasin-3 on neutrophil-mediated atherosclerotic plaque vulnerability and poststroke cerebral injury, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a high number of neutrophils in circulation were shown to be a better means to predict cardiovascular mortality than a high C-reactive protein value [84]. Animal experiments have further demonstrated that by abrogating neutrophil influx into the infarcted hearts of permanent (CCR1 knockout, heterozygous expression of CXCR4, and administration of anti-CCL5 antibodies) or transient LAD-ligated mice (MyD88 knockout, administration of anti-CCL5 antibodies, and Evasin-3 treatment) a reduced infarct size, improved survival, and better cardiac function are achieved [56,57,59,85,86]. Moreover, knockout of MPO in infarcted mice resulted into less adverse remodelling [87].…”
Section: Neutrophilsmentioning
confidence: 99%
“…While the effects of direct targeting of these individual chemokines has not been reported, smaller infarcts following myocardial IR were evident in mice lacking CXCR2,32 the key receptor for the CXCL chemokines, or following a single administration of the CXC chemokine-binding protein, Evasin-3, which prevented CXCL1-induced neutrophil recruitment and reactive oxygen species production in the myocardium 33. Therefore, the reduced levels of CXCL1 and CXCL5 seen in the nitrite-treated patients likely resulted in reduced neutrophil activation, and thus reduction in infarct size.…”
Section: Discussionmentioning
confidence: 95%